Reservoir Studies and Structural Interpretation of 3-D Seismic Data over X-Field, Niger Delta. - SULEMAN Kamaldeen Olasunkanmi (Federal University of Technology Minna., 2023)
Petrophysical analysis and structural interpretation are the essential starting methods for mapping the reservoir distribution. Structural models are developed in this study using 3-D seismic data and analysis of covariance attributes. Well logs and 3-D seismic data were analyzed to identify prolific hydrocarbon intervals. Fault interpretation was enhanced by interpreting vertical sections of covariance attribute. Two horizons, picked at the reservoir level were used for structural modelling. Reserves estimation was obtained at probabilistic levels. Results show that three hydrocarbon bearing reservoirs are present in the field. The prospects consist of vertically stacked oil-saturated sands having an average net thickness of 143 ft. At least two of the oil sands spread from well 3 in the south to other distant wells. In addition, covariance attributes increased the fault population as faults are not very prominent on the seismic data. The structural maps reveal that the area contains normal listric faults that are not extensive in the vertical and lateral direction and are mostly unconnected to one other. The anticlinal structures that can trap hydrocarbon fluids are located in the North. Even though, wells in the southern part of the area have penetrated oil sands, migration is towards the anticlinal structures observed in northern part of the area as there are no sufficient structures in the south. The study concludes that oil sands exist in the region, and they are located within good traps. The limited lateral extent of the first reservoir constrained its recoverable oil amount, estimated at an average value of 394,192 barrels. Nevertheless, the second reservoir is of a high volume, measured at an average estimate of 1,120,779 barrels. The third reservoir has low hydrocarbon saturation. Despite the fragmented fault networks, the substantial presence of valuable oil sands and promising trapping structures in the northern region emphasizes the considerable potential for an expanded exploration and development program within the field.